Two exercises of inflation modelling and forecasting for Azerbaijan - Alexander Chubrik; Gulnar Hajiyeva; Przemysław Woźniak (Center for Social and Economic Research (CASE), 2012)
The paper proposes two econometric models of inflation for Azerbaijan: one based on monthly data and eclectic, another based on quarterly data and takes into account disequilibrium at the money market. Inflation regression based on monthly data showed that consumer prices dynamics is explained by money growth (the more money, the higher the inflation), exchange rate behaviour (appreciation drives disinflation), commodities price dynamics ("imported" inflation) and administrative changes in regulated prices. For the quarterly model, nominal money demand equation (with inflation, real non-oil GDP and nominal interest rate on foreign currency deposits as predictors) and money supply equation were estimated, and error-correction mechanism from money demand equation was included into inflation equation. It is shown that disequilibrium at the money market (supply higher than demand) drives inflation together with money supply growth and nominal exchange rate depreciation and administrative changes in prices. No cost-push variables appeared to be significant in this equation specification. Both models give similar inflation projections, but sudden changes in money demand (2012) lead to significant differences between the projections. It is shown that money is the most important inflation determinant that explains up to 97.8% of CPI growth between 2012 and 2015, and that in order to keep inflation under control the Central Bank of Azerbaijan should link money supply to real non-oil GDP growth.
Keywords: C32; E31; E41; O52; 330; Inflation modelling; Inflation forecasting; Money demand; Money supply; Azerbaijan; Inflation; Ökonometrisches Modell; Prognoseverfahren; Geldnachfrage; Geldmenge; Aserbaidschan